Improving Affordability and Equity in Medicare Advantage. (June 2019) - Song, Zirui; Basu, Sanjay
Facing projected growth in federal deficits, policymakers may increasingly look to Medicare for opportunities to slow spending. Medicare Advantage, which has grown to over one-third of the Medicare population, now costs the federal government over 230 billion a year. Competition in the program is weak in many parts of the country and federal subsidies are distributed unevenly to beneficiaries who are enrolled. This article offers a potential approach toward reforming the Medicare Advantage payment system, which could lower federal costs and enhance equity in the program. It builds a simple framework containing policy options and uses 2015 Centers for Medicare and Medicaid Services data to estimate the stylized impact on federal spending and enrollee benefits.